Influence of cutting parameters and TiBN coating material on the drilling of Al6061-T4 sheets - Aksakal, Bunyamin; Karaca, Faruk (CARL HANSER VERLAG, 2015)
In this study, the machinability of Al6061-T4 aluminum alloy sheets was experimentally investigated by drilling process using uncoated HSS and TiBN coated HSS drill bits. In experiments, the tool feed rate, cutting speed and drill diameter were varied to explore their effects on surface roughness of the machined holes, hole circularity, chip and burr formation, respectively. The hole qualities were determined by using an atomic force microscope (AFM) and a profilometer. The measured values were also analyzed statistically. It was demonstrated that the surface roughness increased with decreasing cutting speed and increased with feed rate of the tool. TiBN coated drill bits provided better hole surfaces compared to uncoated drill bits. The most significant factor on the surface roughness was found to be the cutting speed while the coating material was the second significant factor. In addition, the burst-type burr formations were observed only at a 4 mm drill diameter and high drill speeds with uncoated tools, while the TiBN coated tools gave burr-free surfaces.
Keywords: Al6061-T4; machinability; TiBN coating; surface roughness; burr and chip formation; ALUMINUM; HOLES; Materials Science